2011
DOI: 10.1007/s12548-011-0001-z
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional computerized tomography study into the morphological interrelationship between anterior and posterior guidance and the occlusal scheme in human Caucasian skulls

Abstract: Background The articular eminence of the glenoid fossa together with the occlusal guiding surfaces represent two fundamental determinants of mandibular movement and even though subject to numerous investigations the relationship between both structures still remains unclear today. The purpose of this 3D investigation was to characterize the inclinations of the articular eminence, measure the inclinations of maxillary occlusal guiding surfaces, investigate the occlusal scheme present and examine the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(55 reference statements)
0
0
0
Order By: Relevance
“…Considering that the patients in this study had a mean age Our study found that changes in anterior teeth inclination do not seem to affect the changes in the articular eminence angle. This finding is not consistent with previous reports that found a strong positive correlation between the articular eminence angle and the lingual surface angle of the maxillary incisors [7][8][9]. Overall, our results suggest that changes in the vertical overlap of the maxillary incisors over the mandibular incisors, rather than the inclination of the maxillary incisors, may have a greater impact on the articular eminence angle during orthodontic treatment.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Considering that the patients in this study had a mean age Our study found that changes in anterior teeth inclination do not seem to affect the changes in the articular eminence angle. This finding is not consistent with previous reports that found a strong positive correlation between the articular eminence angle and the lingual surface angle of the maxillary incisors [7][8][9]. Overall, our results suggest that changes in the vertical overlap of the maxillary incisors over the mandibular incisors, rather than the inclination of the maxillary incisors, may have a greater impact on the articular eminence angle during orthodontic treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…Bell and Harris [8] found that the lingual surface angle was, on average, 6.1° steeper than the articular eminence angle. In a more recent study using cone-beam computed tomography (CBCT), it was confirmed that anterior guidance showed slightly higher inclination values than condylar guidance [9].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation